Judaism and Islam, one God one music : the history of Jewish paraliturgical song in the context of Arabo-Islamic culture as revealed in its Jewish Babylonian sources - Rosenfeld-Hadad, Merav (Brill's series in Jewish studies, 2020)
"In Judaism and Islam One God One Music, Merav Rosenfeld-Hadad offers the first substantial study of the history and nature of the Jewish Paraliturgical Song, which developed in the Arabo-Islamic civilization between the tenth and the twentieth centuries. Commonly portrayed as clashing cultures, Judaism and Islam appear here as complementary and enriching religio-cultural sources for the Paraliturgical Song's texts and music, poets and musicians, as well as the worshippers. Relying chiefly on the Babylonian-Jewish written sources of the genre, Rosenfeld-Hadad gives a fascinating historical account of one thousand years of the rich and vibrant cultural and religious life of Middle Eastern Judaism that endured in Arabo-Islamic settings. She convincingly proves that the Jewish Paraliturgical Song, like its people, reflects a harmonious hybridization of Jewish and Arabo-Islamic aesthetics and ideas"--